The Patient–Healthcare Professional Relationship and Communication in the Oncology Outpatient Setting: A Systematic Review. Issue 5 (September 2018) - Prip, Anne; Møller, Kirsten Alling; Nielsen, Dorte Lisbet; Jarden, Mary; Olsen, Marie-Helene; Danielsen, Anne Kjaergaard
Abstract : Background: Today, cancer care and treatment primarily take place in an outpatient setting where encounters between patients and healthcare professionals are often brief. Objective: The aim of this study was to summarize the literature of adult patients' experiences of and need for relationships and communication with healthcare professionals during chemotherapy in the oncology outpatient setting. Methods: The systematic literature review was carried out according to PRISMA guidelines and the PICO framework, and a systematic search was conducted in MEDLINE, CINAHL, The Cochrane Library, and Joanna Briggs Institute Evidence Based Practice Database. Results: Nine studies were included, qualitative (n = 5) and quantitative (n = 4). The studies identified that the relationship between patients and healthcare professionals was important for the patients' ability to cope with cancer and has an impact on satisfaction of care, that hope and positivity are both a need and a strategy for patients with cancer and were facilitated by healthcare professionals, and that outpatient clinic visits framed and influenced communication and relationships. Conclusions: The relationship and communication between patients and healthcare professionals in the outpatient setting were important for the patients' ability to cope with cancer. Implications for Practice: Healthcare professionals need to pay special attention to the relational aspects of communication in an outpatient clinic because encounters are often brief. More research is needed to investigate the type of interaction and intervention that would be the most effective in supporting adult patients' coping during chemotherapy in an outpatient clinic.